Relationships between depersonalization-derealization symptoms and separation anxiety in adult patients with mood and anxiety disorders - Pini, Stefano; Nardi, Benedetta; Carpita, Barbara; Lorenzi, Giada; Mula, Marco; Milrod, Barbara; Massimetti, Gabriele; Cremone, Ivan M.; Bonelli, Chiara; Domschke, Katharina; Schiele, Miriam; Dell’Osso, Liliana; et al. (Frontiers in Psychiatry, 2025)
AimsTo establish the relationship between depersonalization/derealization symptoms (DPs), as assessed by different standardized DP scales, and separation anxiety in a sample of outpatients with anxiety and mood disorders as a primary diagnosis (n=156). We hypothesized that patients with high levels of separation anxiety had more frequent, severe, and clinically relevant DP symptoms than those with low levels of separation anxiety.MethodsA consecutive sample of 156 outpatients with mood and anxiety disorders was evaluated by the Structured Clinical Interview for Derealization/Depersonalization Spectrum (SCI-DER), the Cambridge Depersonalization Scale (CDS), the Body Sensation Questionnaire (BSQ), the Dissociative Experience Scale (DES), the Panic/Agoraphobic Questionnaire-self report (PAS-SR) for the evaluation of separation anxiety.ResultsThe sample was dichotomized into a group with high levels of separation anxiety (3 or more DSM-IV diagnostic items endorsed) vs. those with low levels of separation anxiety (less than 3 items endorsed) by PAS-SR ‘Separation Anxiety’ domain scoring. Patients with high separation anxiety scored significantly higher in all DPs scales compared to the low-separation anxiety group. Derealization was significantly correlated with suicidal ideation (p<.001) and overall suicidality (p<.01). Auto-psychic depersonalization, intended as the feeling unfamiliarity of the self in terms of sensation of being an outside observer of one’s mental process, appeared to exert a significant effect on both suicidality (p<.01) and depression (p<.01).ConclusionsOur findings highlight a link between separation anxiety and DP symptoms. This connection contributes to understanding and evaluating suicidality in individuals with mood and anxiety disorders.